Another world and ours - Smith, Charles Chrisfield (My University, 1894)
Introduction: A study of space and its occupants has long interested the minds of men, and there has always been a reward of knowledge for the interested and careful observer in this, as in other lines. The desire for knowledge of our neighboring worlds called for the invention of the telescope, and this invention, in return, gave the study of heavens its most valuable aid and an unprecedented impetus. Since this invention an immense amount of information has been gathered on the subject- more, in fact, than can be comprehended by any one mind, in one short life time and as yet, only a small part is known of all that there is to be known on this subject. The subject of astronomy is too broad to be treated in this small volume: the sub-subject of the planets of our solar system is perhaps the most noticeable division of the theme, but even this is too extensive for this treatise, so we will confine ourselves to an extended view of a single planet, one of which enough is known to make an interesting study, and not enough to make it seem like a study of the earth. This planet is particularly interesting to us; on account of its close resemblance of our earth, in physical conditions and in habit. Its surface, like that of earth, is made up of land and water, and in about the same proportion. This is according to the best authorities, who consider the red parts land and the rest water, though some claim the opposite, that is, that the red areas are water and the lighter colors show land.
Citation: Smith, Charles Chrisfield. Another world and ours. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Astronomy; Mars; Earth; Space; Theses; Manuscripts (documents)